New Age, new religious movements and the youth: Effects of derationalization of everyday consciousness in the post-secular society - T. A. Khagurov; M. G. Rudakov (RUDN journal of Sociology, 2025)
The article considers history, prerequisites and consequences of the spread of New Age ideas and practices in contemporary society as a new form of spirituality that contributes to the emergence and spread of new religious movements (NRMs). The authors note that in the post-secular society, religious consciousness, (para) religious ideas and practices have become significant factors in social processes. While traditional religions lose their significance, there is an increasing influence on everyday consciousness of various esoteric and occult ideas and practices due to the impact of New Age spirituality on contemporary culture. The origins of such processes can be traced back to the second half of the 19th century - fashion for occultism and esotericism among the European and American intelligentsia and emergence of international religious movements of a new type (Baha’is in Iran, Mormons and Jehovah’s Witnesses in the USA, etc.). These forms of spirituality received a new impetus in the second half of the 1960s-1970s under the countercultural revolution which gave rise to mass fascination with “alternative spirituality” among students. In Western sociology, these processes were called “occult revival”. The authors consider features of nontraditional spirituality in Russia - from the emergence of such fashion among the intelligentsia in the 1970s to the mass wave of esotericism that swept over the Russian society in the 1990s. When speaking about the current situation, the authors emphasize the role of the Internet in the spread and formation of new religious movements, communities and ideologies and note the network nature and the lack of clear institutional boundaries in (para) religious communities. The article presents grounds for classifying NRMs and explains their influence on various spheres of culture and mass consciousness, which is the growing de-rationalization of everyday consciousness as eclectically combining elements of scientific, religious and occult pictures of the world.